Pemanfaatan Media Sosial Instagram dalam Membangun Personal Branding - Arviane Dahniarny Bahar; Yogi Maringgi; Fahria Syawal (Journal of Management and Bussines (JOMB), 2022)
The purpose of this study is to describe the use of Instagram social media in building Personal Branding from Doctor Ayman Alatas. This research method is a qualitative method by analyzing @aymanlatas Instagram content. The researcher describes the personal branding process by using the personal branding concept proposed by Robert Montoya. The results showed that there were three types of content uploaded by Doctor Ayman Alatas. The content is, a) content regarding daily activities, namely in carrying out their activities as a model as well as a doctor; b) content related to education on health issues; c) entertainment content. The personal branding aspect carried out by Doctor Ayman Alatas consists of 8 aspects as follows, a) specialization; b) consistency; c) differentiation; d) leadership; e) personality; f) unity; g) constancy; h) good intentions. In conclusion, from these eight aspects, Doctor Ayman shows that he wants to be known as a young millennial doctor who is witty, close to his family, has broad abilities in the health sector and also shows his Arabic blood. This was then consistently demonstrated by Doctor Ayman Alatas in the content uploaded on Instagram. Keywords: Ayman Alatas, Young Doctor, Instagram, Social Media, Personal Branding